Micropropagation of Prosopis chilensis (Mol.) Stuntz from young and mature plants - Caro, Luis Alberto (2002)
Prosopis chilensis (Mol.) Stuntz (Algarrobo de Chile) is an important native tree species that can be grown in arid and semiarid regions for wood and forage production and environmental protection. Developing a simple and reliable in vitro protocol for cloning it would enable to improve it genetically. Explants of P.chilensis were taken from 4 months-old plants grown in the greenhouse or from adult trees grown in a natural environment. Nodal segments 1 ? 2 cm long containing an axillary bud were selected from elongating shoots. These cuttings were aseptically cultured on two agar-solid basal media, MS or BTMm, and treated with 0.05 mg L-1 BA and 3 mg L-1 of either IAA, IBA or NAA. Sucrose (3% w/v) was used as carbon source. The percentage of sprouted cuttings and whole plant regeneration as well as its shoot and root length were recorded. Number, length and dry weight of shoots and roots were also measured. Rooting was successfulwith cuttings taken from young or adult plants, but explants from young plants showed a better response.Culturing in BTMm resulted in significantly greater shoot and root biomass than culturing in MS. Moreover, this response was higher in young explants when IBA was used as growth regulator. This paper reports a simple and effective method to micropropagate P. chilensis from young and adult plants.